In Vitro Digestibility and Fermentation Products From Rice Straw Silage with Rumen Liquid Addition - I K. T. A., Saputra; Trisnadewi, A. A. A. S; Cakra, I G. L. O. (Jurnal Peternakan Tropika, 2019)
This study aims to determine in vitro digestibility and fermentation products from making rice straw silage with rumen liquidaddition.Silage making conducted in Sidemen Village, Karangasem Regency, and silage analysis was carried out at the Animal Nutrition and Feed Laboratory, Faculty of Animal Husbandry, Udayana University for six (6) months, from June 2018 to December 2018.The design used completely randomized design (CRD) with four treatments and four replications the treatments were A (rice straw without rumen liquid), B (rice straw + 50 ml sterile rumen liquid/kg straw), C (rice straw + 25 ml fresh rumen liquid/kg straw + 25 ml sterile rumen fluid/kg straw), D (rice straw + 50 ml fresh rumen liquid/kg straw).Variables observed were dry matter digestibility, organic matter digestibility, pH, NH 3 , and VFA. The results showed that dry matter digestibility, organic matter digestibility, NH 3 , and VFA in treatments A, B, C, and D were significantly different (P<0,05), whereas for pH values ??not significantly different (P>0,05). It can be concluded that rumen liquid addition of making rice straw silage could increase the dry metter digestibility, organic matter digestibility, NH 3 and VFA and not affected the pH value. Keywords : rice strawsilage, rumen liquid, in vitro digestibility, fermentation products